Pengaruh Kinerja Keuangan Perbankan Terhadap Dana Pihak Ketiga Pada Perusahaan Yang Terdaftar Di BEI Periode 2017-2021 - Af-Ali, Siti Astina; Antu, Cindrawati; Midu, Imelisa; syana D. Pongoliu, Yayu I (Politeknik Negeri Jakarta, 2023)
The aims of this study to examine the effect of banking financial performance consisting of capital adequacy ratio, return on assets, operational efficiency ratio and loan to deposit ratio on third-party funds of banking companies listed on the Indonesian stock exchange for the 2017-2021 period. The method of research used is quantitative with sampling technique in this study uses the purposive sampling method, in order to obtain as many as 215 data from 43 samples. The data used in this study is secondary data in the form an annual report. The meth-od used is multiple linear regression analysis processed using Eviews. The result of this study indicate that the variable capital adequacy ratio and loan to deposit ratio has no effect on third-party funds, while return on asset and operational efficiency ratio affect the third-party funds.